Electrolyte solution, secondary battery, and electric device
By adding thiazolyl compounds to the secondary battery electrolyte, the acid removal effects of silicon and thiazolyl groups are used to solve the problem of acid production and accumulation in the electrolyte, and the stability of the electrolyte and the circulation performance of the secondary battery are improved.
Patent Information
- Application Number
- CN202510363924.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-05-09
AI Technical Summary
The generation and accumulation of acidic substances during storage or use of existing secondary battery electrolytes, which affects the chemical stability of the electrolyte and the cyclic stability of the secondary battery.
Thiazolyl compounds are added to the electrolyte. The thiazolyl compounds have silicon groups and thiazolyl groups. When they are controlled within the preset range, these two functional groups play a role in the acid removal process to achieve efficient and sufficient acid removal and water removal effects.
By reducing the content of trace water and hydrofluoric acid in the electrolyte, the chemical stability and storage quality of the electrolyte are improved, the corrosion of the electrolyte phase interface film of the electrode electrolyte of the secondary battery is reduced, and the circulation stability performance of the secondary battery is improved.
Smart Images

Figure CN119965362A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to an electrolyte, a secondary battery and an electrical device. Background Art
[0002] Secondary batteries, such as lithium-ion batteries, are widely used in portable electronic devices, electric vehicles and energy storage systems due to their high energy density and long cycle life. The cycle stability of secondary batteries is related to the service life of electrical devices. However, during the storage or use of the electrolyte of current secondary batteries, acidic substances are generated and accumulated. These acidic substances not only affect the chemical stability and quality of the electrolyte itself during storage, but also cause corrosion of the electrode electrolyte interface film (such as SEI film) during the use of the secondary battery, accelerate the degradation of the secondary battery, and affect the cycle stability of the secondary battery. Summary of the invention
[0003] In view of this, the present application provides an electrolyte, a secondary battery and an electrical device to solve at least one of the above technical problems.
[0004] To achieve the above objectives, in a first aspect, the present application provides an electrolyte, including a lithium salt and a non-aqueous solvent, the electrolyte also includes a thiazole compound, and the general structural formula of the thiazole compound is: Among them, R1~R3 are each independently selected from one or more of silicon-containing groups, -H, -CH3, -CF3, -OCH3, -C(CH3)3, -SO2CF3 and -COOC(CH3)3, and at least one of R1~R3 includes a silicon-containing group; and based on the mass of the electrolyte, the mass proportion of the thiazole compound is 0.2% to 2%.
[0005] In some possible implementations, based on the mass of the electrolyte, the mass of the thiazole-based compound accounts for 0.5% to 1%.
[0006] In some possible implementations, the electrolyte further includes a carbon-carbon double bond compound, and the carbon-carbon double bond compound includes one or more of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, and vinyl sulfate.
[0007] In some possible implementations, the mass ratio of the carbon-carbon double bond compound to the non-aqueous solvent is 0.1% to 2%.
[0008] In some possible implementations, the mass ratio of the carbon-carbon double bond compound to the thiazole compound is (0.5-5):1.
[0009] In some possible implementations, the general structural formula of the silicon-containing group is -SiR3, wherein R is selected from one or more of -H, -CH3, -CF3, -OCH3, -C(CH3)3, -SO2CF3 and -COOC(CH3)3.
[0010] In some possible implementations, the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 2 mol / L, and the lithium salt includes one or more of LiPF6, LiFSI, LiPO2F2, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiDFOB, LiN(SO2CF3)2 and LiN(SO2F)2.
[0011] In some possible implementations, the non-aqueous solvent includes one or more of C3-C5 carbonates, C2-C6 carboxylates, and C4-C10 ethers.
[0012] In a second aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet, and the secondary battery also comprises the above-mentioned electrolyte.
[0013] In a third aspect, the present application provides an electrical device, which includes the secondary battery mentioned above.
[0014] The thiazolyl compound in the electrolyte of the present application has a silicon group and a thiazolyl group. When the thiazolyl compound is controlled within a preset range, these two functional groups will play a role in the deacidification process to achieve a more efficient and sufficient deacidification and dewatering effect. First, the silicon group reacts with hydrofluoric acid to generate a fluorinated silicon-based product and thiazole, which achieves the purpose of removing hydrofluoric acid for the first time. At the same time, the silicon group can also react with water to generate silicon-based alcohols and thiazoles. After the trace water reaction is reduced, it is beneficial to limit the subsequent side reactions of producing hydrofluoric acid. Secondly, the thiazolyl group and the thiazole produced by the above reaction are Lewis basic groups, which can react with acidic hydrofluoric acid to achieve the purpose of removing hydrofluoric acid for the second time. In addition, the nitrogen element of the thiazolyl group has a lone pair of electrons, which can be complexed with PF5, which is beneficial to suppress the occurrence of side reactions and block the hydrofluoric acid produced by side reactions. Therefore, the silicon-based and thiazolyl dual functional groups work simultaneously in the process of removing hydrofluoric acid from the electrolyte, which is beneficial to more efficiently and fully reduce the content of trace water and hydrofluoric acid in the electrolyte, thereby helping to improve the chemical stability of the electrolyte, improve the storage quality of the electrolyte, and help reduce the corrosion of the resulting secondary battery electrode electrolyte interface film (such as SEI film), thereby improving the cycle stability performance of the resulting secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The hydrofluoric acid nuclear magnetic resonance F spectrum test spectrum of the electrolyte provided in Examples 1-2 and Comparative Example 1 of the present application after being placed in the air for 7 days.
[0016] Figure 2 The battery capacity retention rate test results of the button batteries provided in Examples 1-2 and Comparative Example 1 of the present application after 100 cycles in the 3V-4.6V voltage window.
[0017] Figure 3 Transmission electron microscope images of the interface film on the positive electrode surface of the button-type battery provided in Example 1 and Comparative Example 1 of the present application after 100 cycles in the 3V-4.6V voltage window. DETAILED DESCRIPTION
[0018] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are explained in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0019] In view of the phenomenon of the generation and accumulation of acidic substances in the existing secondary battery electrolyte, the study found that the commonly used lithium salt lithium hexafluorophosphate (LiPF6) in the lithium-ion battery electrolyte will react with trace water to generate PF5 and hydrofluoric acid (HF), and PF5 is a Lewis acid, which will continue to induce side reactions to produce more HF. Therefore, in the presence of trace water, the electrolyte is easily accumulated after long-term storage, or under conditions such as circulation and overcharging during battery operation. Therefore, in order to improve the adverse effects of this phenomenon, feasible strategies include adding additives with water removal or acid removal effects to the electrolyte. In the related art, the water removal or acid removal efficiency of additives is low, and the removal of water or acid is not sufficient, or new reactive substances will still be generated to continue to damage the relevant materials of the secondary battery, resulting in the difficulty in improving the stability of the secondary battery; and increasing the amount of additives to make up for the lack of efficiency cannot fundamentally solve the problem of low water removal or acid removal efficiency of the above-mentioned additives. On the contrary, excessive additives may also affect the conductivity of the electrolyte, ion mobility and the overall performance of the battery. In addition, some acid and water removal additives, such as isocyanate additives, are highly toxic substances, which pose a potential major risk to the health of practitioners and are not suitable for industrial production.
[0020] Based on this, the present application provides an additive that, when added to the electrolyte of a secondary battery, can remove the hydrofluoric acid generated during the use of the electrolyte, reduce the accumulation of hydrofluoric acid, and help achieve efficient water and acid removal effects, thereby achieving the purpose of improving the chemical stability of the electrolyte storage and improving the cyclic stability performance of the secondary battery.
[0021] One embodiment of the present application provides an electrical device, which includes a secondary battery, so that the electrical device has a long service life. For example, the electrical device can be a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery or a lithium-ion capacitor, etc.
[0022] The secondary battery comprises a housing, an electrode assembly and an electrolyte, and the housing may be a packaging bag encapsulated by a packaging film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it may also be a steel-shell battery, an aluminum-shell battery, etc. The secondary battery may be a lithium-ion battery.
[0023] The electrode assembly and the electrolyte are located in the housing, and the electrode assembly includes an electrode sheet and a separator. The electrode sheet includes a positive electrode sheet and a negative electrode sheet. The separator is used to separate the positive electrode sheet from the negative electrode sheet and can be provided between the positive electrode sheet and the negative electrode sheet. In some embodiments, the electrode assembly can be a laminated structure, for example, it is formed by alternating stacking of positive electrode sheets, separators and negative electrode sheets in sequence. In other embodiments, the electrode assembly can also be a winding structure, for example, it is formed by stacking a positive electrode sheet, a separator and a negative electrode sheet in sequence and then winding. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet. When the secondary battery is charged, active ions (such as lithium ions) are released from the positive electrode material of the positive electrode sheet, pass through the separator through the electrolyte, reach the negative electrode sheet and are embedded in the negative electrode material. When a secondary battery is discharged, active ions (such as lithium ions) are released from the negative electrode material of the negative electrode sheet, pass through the isolation membrane through the electrolyte, reach the positive electrode sheet and are embedded in the positive electrode material. Electrons correspondingly travel from the negative electrode sheet through the external circuit to the positive electrode sheet, forming a current flowing from the positive electrode to the negative electrode, supplying power to the electrical device.
[0024] Positive electrode
[0025] The positive electrode sheet includes a positive electrode current collector and a positive electrode material active layer disposed on at least one surface of the positive electrode current collector. The positive electrode current collector may be aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0026] The positive electrode material active layer includes a positive electrode material, and the positive electrode material includes a compound that can reversibly insert and extract lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive electrode material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).
[0027] The positive electrode material active layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode material active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.
[0028] The positive electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0029] Negative plate
[0030] The negative electrode sheet includes a negative electrode current collector and a negative electrode material active layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0031] The negative electrode material active layer includes a negative electrode material, and the negative electrode material includes a carbon material, a silicon material, a silicon-carbon composite material, SiOx (0.5 < x < 1.6), a Li-Sn alloy, a Li-Sn-O alloy, Sn, SnO, SnO2, a spinel structured lithium titanate, and a lithiated TiO2-Li4Ti5O 12 , Li-Al alloy and at least one of metallic lithium.
[0032] The negative electrode active material layer also includes a binder to bond the negative electrode active material particles to facilitate the formation of a film layer, and can also improve the binding force between the negative electrode active material layer and the negative electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin or nylon, etc.
[0033] The negative electrode active material layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0034] Isolation film
[0035] The isolation membrane includes a membrane layer with a porous structure, and the material includes but is not limited to at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the isolation membrane can be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite membrane.
[0036] Electrolyte
[0037] The electrolyte includes a lithium salt and a non-aqueous solvent, and the electrolyte also includes a thiazole compound, and the general structural formula of the thiazole compound is: Wherein, R1 to R3 are independently selected from one or more of silicon-containing groups, -H, -CH3, -CF3, -OCH3, -C(CH3)3, -SO2CF3 and -COOC(CH3)3, and at least one of R1 to R3 includes the silicon-containing group; and based on the mass of the electrolyte, the mass proportion of the thiazolyl compound is 0.2% to 2%. For example, the mass proportion of the thiazolyl compound in the electrolyte can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any value within the range formed by any two of the above values.
[0038] The thiazole compound in the electrolyte of the present application has a silicon group and a thiazole group. When the thiazole compound is controlled within a preset range, these two functional groups will play a role in the acid removal process to achieve a more efficient and sufficient acid removal and water removal effect. Therefore, the corrosion phenomenon of the electrode electrolyte interface film (SEI film) of the above-mentioned secondary battery during use is significantly reduced, so that the above-mentioned secondary battery has good cycle stability, which is conducive to extending the service life of the above-mentioned electrical device.
[0039] Among them, the silicon group will first react with hydrofluoric acid to generate fluorinated silicon-based products and thiazole, achieving the purpose of removing hydrofluoric acid for the first time. At the same time, the silicon group can also react with water to generate silicon-based alcohols and thiazole. After the trace water reaction is reduced, it is beneficial to limit the subsequent side reactions of producing hydrofluoric acid. Secondly, the thiazole group and the thiazole produced by the above reaction are Lewis basic groups, which can react with acidic hydrofluoric acid to produce acid-base reactions, achieving the purpose of removing hydrofluoric acid for the second time. In addition, the nitrogen element of the thiazole group has a lone pair of electrons, which can be complexed with PF5, which is beneficial to inhibit the occurrence of side reactions and block the hydrofluoric acid produced by the side reactions. Therefore, the silicon-based and thiazole-based bifunctional groups work simultaneously in the process of removing hydrofluoric acid from the electrolyte, which can more efficiently and fully reduce the content of trace water and hydrofluoric acid in the electrolyte, thereby helping to improve the chemical stability of the electrolyte, improve the storage quality of the electrolyte, and help to reduce the corrosion of the obtained secondary battery electrode electrolyte interface film (SEI film), thereby improving the cycle stability performance of the obtained secondary battery.
[0040] In some embodiments, based on the mass of the electrolyte, the mass ratio of the thiazolyl compound is 0.5% to 1%. For example, the mass ratio of the thiazolyl compound in the electrolyte can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any value within the range formed by any two of the above values. Controlling the mass ratio of the thiazolyl compound in the electrolyte within the above range is beneficial to further improve the removal efficiency of hydrofluoric acid in the electrolyte, thereby further reducing the deterioration of the electrolyte quality or the risk of corrosion of the SEI film on the electrode surface.
[0041] The applicant also found that the initial hydrofluoric acid content in the electrolyte is generally 10 ppm to 200 ppm. When the mass ratio of the above thiazolyl compound in the electrolyte is 0.2% to 2%, the content of the thiazolyl compound in the electrolyte (defined as a, where a is 0.2 to 2) and the initial hydrofluoric acid content (defined as b, where b is 10 to 200) satisfy 0.05 < b / (100*a) < 10. At this time, the hydrofluoric acid in the electrolyte can be efficiently removed, and the secondary battery has a stable operating effect. Moreover, the applicant also found that when the mass ratio of the thiazolyl compound in the electrolyte is too high (greater than 5%), b / (100*a) < 0.05. Although a too high content of the thiazolyl compound in the electrolyte can efficiently remove hydrofluoric acid, it increases the impedance of the secondary battery, which is not conducive to improving the cycling performance of the secondary battery. When the mass ratio of the thiazolyl compound in the electrolyte is too low (less than 0.05%), b / (100*a) > 10. An insufficient amount of the thiazolyl compound is difficult to achieve an efficient hydrofluoric acid removal effect, and the relatively high content state of hydrofluoric acid lasts for a long time, resulting in the deterioration of the electrolyte quality or an increased risk of corrosion of the SEI film on the electrode surface, which is also not conducive to improving the cycling performance of the secondary battery.
[0042] In some embodiments, the electrolyte further includes a carbon-carbon double bond compound, and the carbon-carbon double bond compound includes one or more of vinylene carbonate, vinyl ethyl carbonate, fluorinated ethylene carbonate, and ethylene sulfate. Further including the carbon-carbon double bond compound in the electrolyte can cooperate with the thiazolyl compound within the preset dosage range of the present application, which is beneficial to improving the compactness and stability of the SEI film while removing hydrofluoric acid.
[0043] In some embodiments, the mass ratio of the carbon-carbon double bond compound to the non-aqueous solvent is 0.1% to 2%. For example, the mass ratio of the carbon-carbon double bond compound to the non-aqueous solvent can be 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2% or any value within the range formed by any two of the above values.
[0044] In some embodiments, the mass ratio of the carbon-carbon double bond compound to the thiazolyl compound is (0.5-5):1. For example, the mass ratio of the carbon-carbon double bond compound to the thiazolyl compound can be 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1 or any value within the range formed by any two of the above values. Controlling the mass ratio of the carbon-carbon double bond compound to the thiazolyl compound within the above range is conducive to promoting the synergistic effect of the two, and is conducive to further improving the density and stability of the SEI film by using the carbon-carbon double bond compound as a film-forming agent on the basis of exerting the acid and water removal effect of the thiazolyl compound and reducing the corrosion of the SEI film.
[0045] In some embodiments, the silicon-containing group has a general structural formula of -SiR3, wherein R is selected from one or more of -H, -CH3, -CF3, -OCH3, -C(CH3)3, -SO2CF3 and -COOC(CH3)3. In the thiazolyl compounds of the present application, the above silicon-containing groups can all play a synergistic role in removing acid with the thiazolyl group.
[0046] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 2 mol / L, and the lithium salt includes one or more of LiPF6, LiFSI, LiPO2F2, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiDFOB, LiN(SO2CF3)2, and LiN(SO2F)2. For example, the concentration of the lithium salt in the electrolyte can be 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, or any value within the range of any two of the above values. For example, LiPF6 is selected as the lithium salt because it can provide high ionic conductivity and improve cycle characteristics.
[0047] In some embodiments, the non-aqueous solvent includes one or more of C3-C5 carbonates, C2-C6 carboxylates, and C4-C10 ethers. For example, C3-C5 carbonates may be cyclic carbonates or chain carbonates with 3-5 carbon atoms, including but not limited to ethylene carbonate, vinylene carbonate, vinylethylene carbonate, propylene carbonate, γ-butyrolactone, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate; C2-C6 carboxylates include but not limited to one or more of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and propyl propionate; C4-C10 ethers may be cyclic ethers or chain ethers with 4-10 carbon atoms, including but not limited to one or more of 1,3-dioxolane, 1,4-dioxane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxymethane, 1,2-dimethoxyethane, and diethylene glycol dimethyl ether.
[0048] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0049] Embodiment 1:
[0050] An electrolyte, the preparation method of which comprises: preparing a mixed liquid of EC and EMC in a volume ratio of 3:7, adding 1.2 mol / L lithium hexafluorophosphate, stirring, and adding 1% by weight of compound A, wherein the chemical formula of compound A is Obtain electrolyte.
[0051] Example 2: The difference from Example 1 is that compound A is replaced by compound B, and the chemical formula of compound B is
[0052] Example 3: The difference from Example 1 is that the mass percentage of compound A is adjusted to 0.5%.
[0053] Example 4: The difference from Example 1 is that the mass proportion of compound A is adjusted to 0.8%.
[0054] Example 5: The difference from Example 1 is that the mass percentage of compound A is adjusted to 0.2%.
[0055] Example 6: The difference from Example 1 is that the mass proportion of compound A is adjusted to 2%.
[0056] Comparative Example 1:
[0057] An electrolyte solution, the preparation method of which comprises: preparing a mixed liquid of EC and EMC in a volume ratio of 3:7, adding 1.2 mol / L lithium hexafluorophosphate, stirring, and obtaining the electrolyte solution.
[0058] The present application also assembles the electrolytes obtained in Examples 1-2 and Comparative Example 1 into secondary batteries in a glove box, respectively. The oxygen content in the glove box is less than 1 ppm, and the water content is less than 1 ppm to prevent oxidation and deterioration of the electrolyte. The lithium metal negative electrode, the separator, 60 μL of the electrolyte, and the electrode coated with the NCM811 positive electrode material are assembled in sequence to obtain the button batteries of Examples 1-2 and Comparative Example 1.
[0059] Comparative Example 2: The difference from Example 1 is that the mass percentage of compound A is adjusted to 0.01%.
[0060] Comparative Example 3: The difference from Example 1 is that the mass proportion of compound A is adjusted to 10%.
[0061] Comparative Example 4: The difference from Example 1 is that the mass percentage of compound A is adjusted to 0.1%.
[0062] Comparative Example 5: The difference from Example 1 is that the mass proportion of compound A is adjusted to 3%.
[0063] The present application conducts the following tests on the electrolytes and button batteries obtained in Examples 1-6 and Comparative Examples 1-5:
[0064] 1. The initial hydrofluoric acid content of the electrolyte is tested by nuclear magnetic resonance F spectroscopy and acid-base titration. For Examples 1-6 and Comparative Examples 2-5, the initial hydrofluoric acid content of the electrolyte is measured before adding compound A or compound B. For Comparative Example 1, the initial hydrofluoric acid content of the electrolyte is measured after the electrolyte is prepared. After testing, the initial hydrofluoric acid content of the electrolytes of Examples 1-6 and Comparative Examples 1-5 implemented multiple times is divided into three levels, which are approximately 25.4ppm, 141.1ppm and 2788.8ppm, respectively. Then, 10mL of the electrolytes of Examples 1-6 and Comparative Examples 1-5 are taken respectively and placed in the air for 7 days. The electrolyte will absorb moisture in the air, and the lithium salt will also react with moisture to produce additional hydrofluoric acid. Then, the hydrofluoric acid content in different electrolytes is detected by nuclear magnetic resonance F spectroscopy and acid-base titration. Please refer to Table 1 and Figure 1 .
[0065] 2. The button cells of Examples 1-6 and Comparative Examples 1-5 were respectively placed at 25°C for 12 h, activated at a current density of 0.1C (170 mAh / g), and cycled 100 times at 3V-4.6V at a rate of 1C to test the battery capacity retention rates of different button cells. The test results are shown in Tables 1 and Figure 2 .
[0066] 3. Taking the button-type batteries of Example 1 and Comparative Example 1 after 100 cycles as an example, the thickness of the interface film on the surface of the positive electrode was tested using a transmission electron microscope.
[0067] See also Figure 1 Taking Examples 1-2 and Comparative Example 1 as examples, no additives were added to the electrolyte of Comparative Example 1. On the basis of providing the conditions for the formation of hydrofluoric acid, a hydrofluoric acid signal with a certain relative intensity was detected in the electrolyte through nuclear magnetic resonance F spectrum detection, indicating that the conditions for the formation of hydrofluoric acid can enable the conventional electrolyte to produce additional hydrofluoric acid; thiazole compounds conforming to the preset structural formula, i.e., compound A and compound B, were added to the electrolytes of Examples 1 and 2, respectively. On the basis of providing the same conditions for the formation of hydrofluoric acid, through nuclear magnetic resonance F spectrum detection, the relative intensity of the hydrofluoric acid in the electrolyte of Examples 1-2 was shown to be undetectable, indicating that the electrolytes of Examples 1-2 contained almost no hydrofluoric acid, and the thiazole compounds in the electrolytes could better remove hydrofluoric acid.
[0068] See also Figure 2 Taking Examples 1-2 and Comparative Example 1 as examples, the electrolyte prepared in Comparative Example 1 without any additives has a capacity retention rate of about 11.1% after 100 cycles in the NCM811 / Li button battery, while the electrolytes prepared in Examples 1 and 2 with compound A and compound B added respectively have capacity retention rates of about 95.1% and 82.3% after 100 cycles in the NCM811 / Li button battery, respectively, indicating that the silicon-based and thiazole groups in the preset general structure conforming to compound A and compound B have obvious scavenging effects on hydrofluoric acid during the battery cycle, and have good acid removal effects, thereby being able to maintain the performance of the electrolyte during the cycle.
[0069] See also Figure 3 Taking Example 1 and Comparative Example 1 as examples, the positive electrode surface interface film formed during the cycle of the button battery of Comparative Example 1 is thick and uneven, indicating that the hydrofluoric acid accumulated in its electrolyte has a certain degree of corrosion on the positive electrode surface interface film, which is not conducive to battery cycling. The positive electrode surface interface film formed during the cycle of the button battery of Example 1 is dense and uniform, indicating that the compound A in its electrolyte has a preset general structure, and the silicon group and thiazole group therein can efficiently remove the hydrofluoric acid in the electrolyte, thereby reducing the degree of hydrofluoric acid corrosion of the electrode surface interface film during the cycle of the secondary battery, which is beneficial to improving the cycle performance of the secondary battery.
[0070] Table 1. Test results of hydrofluoric acid content in electrolytes and secondary battery cycle performance of Examples 1-6 and Comparative Examples 1-5 of the present application
[0071]
[0072] The electrolyte of Examples 1-6 of the present application includes a preset content (0.2% to 2%) of a thiazole-based compound containing a silicon group. At this preset content, the two functional groups of the silicon group and the thiazole group play a role in the deacidification process to achieve a more efficient and sufficient deacidification and dewatering effect, which is beneficial to improve the chemical stability of the electrolyte, improve the storage quality of the electrolyte, and help reduce the corrosion of the obtained secondary battery electrode electrolyte interface film (such as SEI film), thereby improving the cycle stability performance of the obtained secondary battery. Among them, Examples 1-4 meet the more preferred preset content (0.5% to 1%), at which The preset content can further improve the removal efficiency of hydrofluoric acid in the electrolyte, thereby further reducing the deterioration of the electrolyte quality or causing the risk of SEI film corrosion on the electrode surface. The electrolyte of Example 1 has a good deacidification effect at different initial hydrofluoric acid levels (25.4ppm, 141.1ppm and 2788.8ppm).
[0073] In addition, the initial hydrofluoric acid of the electrolyte is generally 10 ppm to 200 ppm (such as 25.4 ppm and 141.1 ppm in Table 1). When the initial hydrofluoric acid of the electrolyte is at this level, through the electrolyte technical solution of the present application, a preset content of a thiazole compound containing a silicon group is added to the electrolyte so that b / (100*a) meets the preset range, thereby significantly improving the cycle performance of the secondary battery while removing acid.
[0074] Compared with Examples 1-6, Comparative Example 1 does not add a thiazole compound containing a silicon group, and its electrolyte is generated and accumulated during storage or use. These acidic substances affect the chemical stability of the electrolyte itself during storage and the quality of the electrolyte. They also cause corrosion of the electrode electrolyte interface film (such as the SEI film) during the use of the secondary battery, accelerate the degradation of the secondary battery, and affect the cycle stability performance of the secondary battery.
[0075] Compared with Examples 1-6, the content of the thiazole compound containing silicon groups in the electrolyte of Comparative Examples 2 and 4 is too low, and the removal effect of the acidic substances is poor, resulting in obvious accumulation of acidic substances (such as HF) in the electrolyte, affecting the cycle stability performance of the secondary battery.
[0076] Compared with Examples 1-6, the content of the thiazolyl compound containing silicon groups in the electrolyte of Comparative Examples 3 and 5 is too high. Although it can remove acidic substances, the excessive thiazolyl compound containing silicon groups leads to an increase in the impedance of the secondary battery, resulting in a decrease in the cycle performance of the secondary battery.
[0077] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. An electrolyte comprising a lithium salt and a non-aqueous solvent, characterized in that: The electrolyte further comprises a thiazole compound, and the general structural formula of the thiazole compound is: Among them, R1~R3 are each independently selected from one or more of a silicon-containing group, -H, -CH3, -CF3, -OCH3, -C(CH3)3, -SO2CF3 and -COOC(CH3)3, and at least one of R1~R3 includes the silicon-containing group; and based on the mass of the electrolyte, the mass proportion of the thiazole-based compound is 0.2% to 2%.
2. The electrolyte according to claim 1, characterized in that Based on the mass of the electrolyte, the mass proportion of the thiazole-based compound is 0.5% to 1%.
3. The electrolyte according to claim 1, characterized in that The electrolyte further includes a carbon-carbon double bond compound, wherein the carbon-carbon double bond compound includes one or more of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate and vinyl sulfate.
4. The electrolyte according to claim 3, characterized in that The mass ratio of the carbon-carbon double bond compound to the non-aqueous solvent is 0.1% to 2%.
5. The electrolyte according to claim 3, characterized in that The mass ratio of the carbon-carbon double bond compound to the thiazole compound is (0.5-5):
1.
6. The electrolyte according to claim 1, characterized in that The general structural formula of the silicon-containing group is -SiR3, wherein R is selected from one or more of -H, -CH3, -CF3, -OCH3, -C(CH3)3, -SO2CF3 and -COOC(CH3)3.
7. The electrolyte according to claim 1, characterized in that The concentration of the lithium salt in the electrolyte is 0.8 mol / L to 2 mol / L, and the lithium salt includes one or more of LiPF6, LiFSI, LiPO2F2, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiDFOB, LiN(SO2CF3)2 and LiN(SO2F)2.
8. The electrolyte according to claim 1, characterized in that The non-aqueous solvent includes one or more of C3-C5 carbonates, C2-C6 carboxylates and C4-C10 ethers.
9. A secondary battery comprising a positive electrode sheet, a negative electrode sheet and a separator disposed between the positive electrode sheet and the negative electrode sheet, characterized in that: The secondary battery further comprises the electrolyte according to any one of claims 1 to 8.
10. An electrical device, characterized in that: The electric device comprises the secondary battery as claimed in claim 9.
Citation Information
Patent Citations
Electrolyte and lithium ion battery
CN110391457A
Non-aqueous electrolyte and battery containing non-aqueous electrolyte
CN110400969A
High-voltage lithium ion battery electrolyte film-forming additive, electrolyte and battery thereof
CN111900477A
Non-aqueous electrolyte solution and lithium secondary battery comprising the same
KR1020170038743A